Assessment of the Intellectual Capital of Teacher in Inclusive Education - S. Budovich, L.; B. Nadtochiy, Yu. (International Journal of Engineering and Technology, 2018)
This article is devoted to the assessment of intellectual capital of a teacher in the system of inclusive education. It is indisputable that at present there is no unanimous opinion regarding the approaches to evaluate and the methods used to assess intellectual capital. Based on the review of methods for the evaluation of intellectual capital, methods used often are presented in the context of modernity.The authors have developed a comprehensive assessment of the intellectual capital of a teacher in an educational organization of higher education. The stages of such an assessment are considered in detail: Stage 0 - goals and objectives of the assessment, Stage 1 - teacherâ€™s self-assessment, Stage 2 - experts' assessment, Stage 3 - customers and consumers assessment; Stage 4 - the results of a comprehensive assessment and recommendations.There are many reasons for assessing the intellectual capital of a teacher, one of the main reasons is the constant improvement of the quality of education, which is directly related to modern requirements: expanding the range of educational services and accessibility of education for all (inclusive education).Â Â